2016
DOI: 10.1182/blood.v128.22.2073.2073
|View full text |Cite
|
Sign up to set email alerts
|

Deregulated Expression of Long Non-Coding RNAs UCA1, NEAT1 and BDNF-As in Multiple Myeloma

Abstract: Introduction. Multiple myeloma (MM) is the second most common hematological malignancy in the world. It is characterized by increasing rate of various genetic mutations and dysregulated pathways. This work aims to find out if this phenomenon is also reflected in dysregulation of the so-called long non-coding RNA molecules (lncRNA). These molecules are over 200 nt long and primarily localized in the nucleus. It seems increasingly obvious that lncRNAs play a crucial role in human diseases and during hematopoiesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The brain-derived neurotrophic factor antisense RNA (BDNF-AS) is a naturally conserved lncRNA (located at chromosome region 11p14.1 and with 2036 bp in length) and exerts essential functions in various human diseases [ 14 – 16 ]. A previous study found that BDNF-AS was abnormally up-regulated in MM, and its sensitivity and specificity were very high in discriminating MM from healthy donors [ 17 ]. In addition, Ai et al, revealed that inhibition of BDNF-AS using lentiviral shRNA silencing inhibited MM cell growth and angiogenesis in the bone marrow milieu in vivo [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The brain-derived neurotrophic factor antisense RNA (BDNF-AS) is a naturally conserved lncRNA (located at chromosome region 11p14.1 and with 2036 bp in length) and exerts essential functions in various human diseases [ 14 – 16 ]. A previous study found that BDNF-AS was abnormally up-regulated in MM, and its sensitivity and specificity were very high in discriminating MM from healthy donors [ 17 ]. In addition, Ai et al, revealed that inhibition of BDNF-AS using lentiviral shRNA silencing inhibited MM cell growth and angiogenesis in the bone marrow milieu in vivo [ 18 ].…”
Section: Introductionmentioning
confidence: 99%